iPhone and iPad Apps for Absolute Beginnerse/gif - Lewis, Rory (Apress, 2012)
Let me get this straight: you want to learn how to program for the iPhone or the iPad, and you consider yourself to be pretty intelligent—but whenever you read computer code or highly technical instructions, your brain seems to shut down. Do your eyes glaze over when reading gnarly instructions? Does a little voice in your head chide you, “How about that! Your brain shut down six lines ago, but you’re still scanning the page—pretending you’re not as dense as you feel. Great!” See if you can relate to this…you’re having an issue with something pretty technical and you decide to Google it and troubleshoot the problem. You open the top hit—and somebody else has asked the exact same question! You become excited as the page loads, but, alas, it’s only a bulletin board (a chat site for all those geeks who yap at one another in unintelligible code). You see your question followed by…but it’s too late! Your brain has already shut down, and you feel the tension and frustration as knots in your belly. Sound familiar? Yes? Then this book’s for you! My guess is that you’re probably standing in a bookstore or in the airport, checking out a magazine stand for something that might excite. Because you’re reading this in some such upscale place, you can probably afford an iPhone, a Mac, a car, and plane tickets. You’re probably intrigued by the burgeoning industry of handhelds and the geometric rate at which memory and microprocessors are evolving…how quickly ideas can be turned into startlingly new computing platforms, into powerful software applications, into helpful tools and clever games…perhaps even into greenbacks! And now you are wond